Rancang Bangun Pengatur Suhu Dan Kelembaban Ruang Server Berbasis IoT - Zarkasi, Muhammad Irvan; Endri, Jon; Sarjana, Sarjana (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The development of information technology in this modern era has progressed very rapidly, many ways have been developed to store large amounts of data, one of which is to use a server. A server is a computer system that serves and controls client access that is connected to it. All activities that we do on the internet always involve the server. Servers play a very important role because of their heavy duty to serve clients. Therefore, the server may not experience interference. One of the disturbances that cause a damaged server is the temperature that is too hot so that this tool is made in order to prevent these problems. This tool is made to regulate the temperature and humidity of the server room that exceeds reasonable limits. This tool is made using Arduino Uno as a microcontroller, DHT11 as a temperature and humidity sensor, Ethernet shield as a link to the internet. This tool also uses the Blynk application as monitoring, from the results of reading temperature and humidity sensors on this device can reduce the temperature by 6˚C cooler when the temperature in the room is hot, in this case the tool functions as it should